E-Cordial Labeling for Cupola Graph Cu(3, b, n) - Yulianti, Kartika; Rokhmatillah, Fitri; Sispiyati, Ririn (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2022)
Graph labeling is a map that maps graph elements such as vertices, edges, vertices, and edges to a set of numbers. A graph labeling is named e-cordial if there is a binary mapping f:E(G)→0,1 which induces the vertex labeling defined by g(v)=Ʃ_uvϵE(G)f(uv)(mod 2), so that it satisfies the absolute value of the difference between the number of vertices labeled 1 and the number of vertices labeled 0 is less than equal to 1, and also for the number of edges labeled 0 and labeled 1. A graph that admits the e-cordial labeling is called an e-cordial graph. In this paper, we proved that some of the cupola graph Cu(3,b,n) is e-cordial.Keywords: E-Cordial Labeling; E-Cordial Graph; Cupola Graph Cu(a, b, n). AbstrakPelabelan graf merupakan pemetaan yang memetakan unsur-unsur graf seperti simpul, sisi, simpul dan sisi ke himpunan bilangan. Sebuah pelabelan dinamakan pelabelan e-cordial jika terdapat pemetaan biner f:E(G)→0,1 yang menginduksi pelabelan simpul yang didefinisikan g(v)=Ʃ_uvϵE(G)f(uv)(mod 2) sehingga nilai mutlak dari selisih banyaknya simpul yang dilabeli 1 dan banyaknya simpul yang dilabeli 0 kurang dari sama dengan 1, dan nilai mutlak dari selisih banyaknya sisi yang dilabeli 1 dan banyaknya sisi yang dilabeli 0 kurang dari sama dengan 1. Sebuah graf yang dapat dilabeli secara e-cordial dinamakan graf e-cordial. Pada makalah ini dibuktikan bahwa beberapa graf kubah Cu(3,b,n) adalah e-cordial.Kata Kunci : Pelabelan E-Cordial; Graf E-Cordial; Graf Kubah Cu(a, b, n).